2007
DOI: 10.1097/01.ccm.0000269037.66955.f0
|View full text |Cite
|
Sign up to set email alerts
|

Toward the prevention of acute lung injury: Protocol-guided limitation of large tidal volume ventilation and inappropriate transfusion*

Abstract: Interdisciplinary intervention effectively decreased large tidal volumes and unnecessary transfusion in mechanically ventilated patients and was associated with a decreased frequency of new acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 32 publications
7
102
1
3
Order By: Relevance
“…26,28 Indeed, a quality-improvement intervention aimed at decreasing ventilator tidal volume and liberal transfusion decreased harmful exposures and was associated with a reduced incidence of ARDS in mechanically ventilated patients without ALI at the outset. 29 Our study found that patients with community-acquired ARDS were more likely to be medical patients (85%) with pneumonia (59%), whereas those who developed ARDS after hospital admission were more likely to be surgery patients (54%). TenHoor et al found a proportional mortality ratio (death from ALI vs other causes) of 11.8 (95% CI 3.8 -36.0) with ICD-9 code E870-879.9, "surgical or medical misadventures" such as accidental perforation during medical or surgical care, foreign objects left in body, failure of sterile precautions during a procedure, failure in dosage, contamination of blood or other fluids, and related iatrogenic exposures.…”
Section: Discussionmentioning
confidence: 77%
“…26,28 Indeed, a quality-improvement intervention aimed at decreasing ventilator tidal volume and liberal transfusion decreased harmful exposures and was associated with a reduced incidence of ARDS in mechanically ventilated patients without ALI at the outset. 29 Our study found that patients with community-acquired ARDS were more likely to be medical patients (85%) with pneumonia (59%), whereas those who developed ARDS after hospital admission were more likely to be surgery patients (54%). TenHoor et al found a proportional mortality ratio (death from ALI vs other causes) of 11.8 (95% CI 3.8 -36.0) with ICD-9 code E870-879.9, "surgical or medical misadventures" such as accidental perforation during medical or surgical care, foreign objects left in body, failure of sterile precautions during a procedure, failure in dosage, contamination of blood or other fluids, and related iatrogenic exposures.…”
Section: Discussionmentioning
confidence: 77%
“…2,5,6 Thus, accurate identification of populations at risk for acute organ dysfunction is crucial to improve understanding of the mechanisms involved in the risk and to develop novel therapies for these patients.…”
Section: Case Definitionmentioning
confidence: 99%
“…Clinical and epidemiological studies [6][7][8][9] have indicated that respiratory dysfunction is less likely in patients who have both sepsis and diabetes mellitus than in patients who have sepsis but no diabetes. Possible explanations for this difference include the effects of hyperglycemia on the inflammatory response, metabolic abnormalities in diabetes, and interactions of agents used to treat diabetes mellitus.…”
mentioning
confidence: 99%
“…In our practice we have found that a multidisciplinary educational initiative combined with electronic surveillance for injurious tidal volumes and automated provider alerts can limit patients' exposure to unsafe ventilation and have been associated with lower mortality. 21 Transfusion-related ALI, which is the leading cause of death after blood-product administration, is defined as ALI occurring within 6 hours of blood-product transfusion, in the absence of other risk factors (eg, sepsis, aspiration, or lung contusion). If other risk factors are present when ALI develops within 6 hours, the term "possible transfusionrelated ALI" is employed.…”
Section: Ali As a Preventable Complication Of Critical Illnessmentioning
confidence: 99%